Pemanfaatan Kadaver dalam Pendidikan Kedokteran: Apakah Mutlak? Pembahasan pada Ruang Lingkup Hukum Kesehatan - Gembong Satria Mahardhika; Fitranto Arjadi; Prima Maharani Putri; Abdul Hakim Nitiprodjo (Majalah Kedokteran Indonesia, 2025)
Cadavers retain significant value within the realm of medicine, particularly in the context of anatomy laboratories, where they serve as crucial educational tools. Cadavers are of significant importance in facilitating the educational experience within the anatomy laboratory. Numerous research investigations have indicated that the decrease in anatomical knowledge is purportedly a contributing factor to the rise in “surgical errors” and subsequent surge in medicolegal litigation. Utilisation of cadavers for medical education and research should be conducted in a discerning, proficient, and optimal manner. At the fundamental level, individuals can access educational materials from sources such as prosection, plastination, or anatomy museums. The primary focus in higher education is placed on cadaveric dissection, particularly in relation to the development of clinical skills relevant to surgical practise.